Assessing the sustainability of the blue swimming crab (Portunus pelagicus) on the Eastern Coast of Lampung: a holistic approach to conservation and resource stewardship - Yulianto, Herman; Ihsan, Yudi Nurul; Sumiarsa, Dadan; Ansari, Andrianto; Hendarmawan, (Frontiers in Marine Science, 2024)
In response to the escalating demand for blue swimming crabs (BSC) and the consequential impact on their habitat and population, this study advocates for sustainable management through a holistic approach. Our comprehensive framework integrates ecological conservation, socioeconomic well-being, and governance principles, aiming to establish a policy framework for the sustainable management of BSC in the Eastern Coast of Lampung. The research emphasizes the urgent issue of overexploitation, with an exploitation rate of 0.71, requiring immediate attention to prevent stock depletion and maintain ecosystem health. Findings reveal that male BSC, measured by carapace width, typically reaches the length at first catch (Lc50) at approximately 118.69 mm, while for females, it is about 122.70 mm—indicating that BSC is often caught larger than the 10 cm legal requirement set by the Ministry of Marine and Fisheries of Indonesia. Economic analysis demonstrates the profitability of the blue swimming crab business on Lampung's east coast, with a favorable crab capture per trip (4.63) and total costs ratio (1.18). The study area, featuring an extensive mangrove forest, hosts a crucial crustacean population, contributing significantly to BSC's diet. Beyond ecological significance, mangrove conservation enhances our understanding of environmental sustainability, particularly in carbon stock contributions. Addressing sustainability challenges requires a multi-faceted approach, including precise fishing technologies, effective regulation enforcement, and improved monitoring. Collaborative efforts among government authorities, fishing communities, and conservation groups are essential for balancing economic interests with the long-term ecological health of BSC populations in the study area.